Using Health Belief Model as a theoretical basis for Implementation of Health Protection Strategies among School Children in the Post COVID 19 Era: Implications for Health Education - Ejimonu, Ngozi Constance; Okeke, Kalu Mgbo; Eze-Ufodiama, Stella Chiamaka (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
Infectious diseases are common health problems affecting school children in this dispensation. Amidst the innumerable infectious diseases, COVID-19 is the most dreadful. This disease affects all human species, irrespective of age, level or class. COVID-19 disease is caused by a virus named SARS-Cov2, which deleteriously hampers academic progress of school children due to severe complications underlying COVID-19 incidence. In the Post COVID-19 Era, the use of Health belief model through health protection strategies is necessary to effectively manage the spread of the disease and other infectious disease that may arise among the school children. The paper however, examined health protection strategies such as planning and preparedness; prevention and early detection; investigation and control; wider public health management and leadership this is aimed to further reduce the impact of COVID-19 in this Post COVID-19 Era by assessing the implication of health education for school children. It was concluded that health protection strategies could help prevent the spread of diseases in the post COVID-19 era; also it was recommended that health protection strategy should be encouraged through health education among school children.